Arabic language sustainability and wellbeing: a language policy in the poetry of Nizar Qabbani - بيطار , لجين (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research aims to formulate a language policy that respond to understand the Arabic human legacy and acknowledges the significance of human's land-nation bond as a growth's prerequisite and to be maintained as an applicable mechanism in society. It is noteworthy to feature the policy of Arabic language sustainability and wellbeing in Nizar Qabbani poetry, which has useful intellectual impact and psychological well-being on the people who adopt and excel this type of literature and on the coming generation later on. Venturing beyond artistic stereotype, the language policy of Nizar's poetry insists to express human needs and individual motivational and balanced standards. So, this policy attempts to crash the verbal structure as well as borrowed, created and modified some of human principles. It also has a role in discipline control social behaviour that human continuously adopted paying no attention to the harm that opposes human well-being. Arabic language sustainability and wellbeing contain physical and development scenes shown as an artistic tool that contributes in building wellbeing human personality that is able to direct and lead the language on the track that insure language sustainability and competitiveness.